Which Pain Rehabilitation Programme Should Patients With Chronic Back Pain Attend? - A Practical Example of a Service Evaluation Based Upon Implementing Research Findings into Clinical Practice - Karen L Barker; Leila Heelas; Elaine Buchanan; Fran Toye (Journal of Novel Physiotherapy and Physical Rehabilitation - Peertechz Publications, 2014)
Background: To evaluate a service reconfiguration of pain rehabilitation programmes for chronic back pain using three programmes of differing intensity and duration and a clinical algorithm. This study describes the outcomes for each programme for three consecutive cohorts.  Method: Non randomised observational study of 120 consecutive patients with chronic pain treated by a Physiotherapy Department of a Specialist Orthopaedic and Rehabilitation hospital. Three different pain rehabilitation programmes each comprising of multidisciplinary rehabilitation with varying intensity and duration of content were compared for clinical and cost efficacy. The main outcomes used were Oswestry Disability Index (ODI), Pain visual analogue score (VAS), pain catastrophising scale (PCS), pain self efficacy questionnaire (PSEQ), Tampa scale for kinesiophobia (TSK) and physical tests of timed sit to stand and 5 minute walk test. Results: Analysis of changes within groups was by Wilcoxon signed rank tests and found patients attending the 'gold standard' Functional Restoration Programme showed statistically and clinically significant improvements in mean change scores for VAS, PCS, TSK, PSEQ, sit to stand and 5 minute walk test - p<0.001; with effect sizes for the different outcomes ranging from 0.2-1.19. For the shorter Active Rehabilitation Programme there were significant improvements all outcomes except TSK and sit to stand (p0.004), with effect sizes varying from 0.48-0.81. For the Short Management Programme there were significant improvements all outcomes with effect sizes ranging from 0.18-1.14.  Conclusion: This research uses a novel approach where an existing service was redesigned adhering to key principles but varying intensity and duration and using a clinical algorithm to determine treatment allocation in order to translate research based findings into clinical practice.